The Development of Financial Accounting Learning Tools with Gall and Borg Model - Putri, Reni Sovia; Wardoyo, Cipto (Dinamika Pendidikan, 2017)
This research aims to develop financial accounting learning tools namely; development of lesson plan, handouts, and learning media. The object of this research was the 11th grade students of accounting study program in Muhammadiyah 03 High Vocational School Singosari. The model of learning device development used Gall and Borg model. The stages were 1) Initial Needs Analysis; 2) Initial Product Developing; 3) Validation; 4) Product Revision I; 5) Limited Field Trial; 6) Product Revision II; 7) Field Trial; and 8) Final Product. The result of the research shows that the learning tools on financial accounting subject are valid/proper to be used. It is Ã‚Â proven by the score of material expert judgment that is 82.8%, by the media expert that is 98.6%, by the education expert that is 86%, by the limited field trial (students and teachers ) that are 87.7% and 80.7%, and by Field trials that is 80.2%. In field trials, the development of learning tools can improve student learning outcomes. There are only 3 students who got their grades below the minimum mastery standard.